Rainwater harvesting and storage systems for domestic supply: an overview of research for water scarcity management in rural areas - Valdiviezo Gonzales, Lorgio Gilberto (2023)
This article aimed to carry out a systematic review of rainwater harvesting and storage systems (RWHSS) between 2012 and 2022. This study used the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement (PRISMA) as reviewing method. The systematic review process involved four stages: identification, screening, eligibility and inclusion. To carry out this research, the Scopus, ScienceDirect and Springer Link digital databases were consulted using the keywords “rainwater”, “storage”, “harvesting”, “rural”, “treatment”; initially obtaining 581 results, after filtering the information through PRISMA, 15 articles were obtained to carry out the analysis of the results linked to the questions raised in this work. The results showed that all the RWHSS have four main components: 1) Catchment area, 2) gutters, 3) pipes and 4) storage system. Regarding the most used material in the system’s catchment area, it is galvanized metal with 25.71% of the studies and for the construction of the cistern, it is concrete with 41.66%. The quality of the rainwater collected in the RWHSS varies according to some factors such as the material, maintenance, weather conditions, etc. The main rainwater quality parameters considered by the authors at the time of implementing and using an RWHSS were identified, and compliance of the parameters with the WHO standard values was also evaluated. The main parameters considered by the authors were: pH (66.66%), turbidity (53.33%), E. Coli (53.33%), lead (40%) and nitrates (40%).